2020
DOI: 10.1038/s41598-020-65061-6
|View full text |Cite
|
Sign up to set email alerts
|

ERK Activity in Immature Leukemic Cells Drives Clonal Selection during Induction Therapy for Acute Myeloid Leukemia

Abstract: Selection of resistant clones following intensive chemotherapy is a common obstacle for cure in many cancers, particularly in acute myeloid leukemia (AML). In AML, clone-specific sensitivity to chemotherapy varies even within the same patient. Multiple mutations and genetic aberrations are associated with clones surviving chemotherapy. The current study explored the role of activated signaling pathways in chemoresistance as a function of cell maturation, reflected by CD34 expression. In-vitro, Kasumi-1 leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…7f ). The ERK pathway has been shown to drive the selection of resistant clones during induction therapy for AML in vitro and elevated ERK1/2 activity has also been observed in AML patients who have developed resistance to FLT3-targeted inhibitors 27 , 28 . Expression of p38 has also been shown to drive chemotherapy resistance in different cancers 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…7f ). The ERK pathway has been shown to drive the selection of resistant clones during induction therapy for AML in vitro and elevated ERK1/2 activity has also been observed in AML patients who have developed resistance to FLT3-targeted inhibitors 27 , 28 . Expression of p38 has also been shown to drive chemotherapy resistance in different cancers 29 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent in vitro study, 17 midostaurin has been reported to inhibit several signaling pathways, including the ERK pathway. Our previous study has demonstrated a critical role of ERK activation in clonal selection and enhancement of chemo‐sensitivity by direct ERK inhibition 18 . The efficacy of midostaurin in high‐AR cases may therefore be attributed to co‐inhibition of FLT3, at the receptor level, and of downstream kinases like ERK.…”
Section: Discussionmentioning
confidence: 98%
“…p-ERK1/2 has previously been shown to be upregulated in CD34+ cells compared CD34cells. 31 10 patients had CD34+ cells in MC9, most of them (7/10) were in the high 24h-p-ERK1/2 group (Supplementary Fig. 9b).…”
Section: Signaling In Cd34+ Mc1 Aml Blast Clustermentioning
confidence: 97%
“…29,30 The ERK pathway has been shown to drive selection of resistant clones during induction therapy for AML in vitro and elevated ERK1/2 activity has also been observed in AML patients who have developed resistance to FLT3-targeted inhibitors. 31,32 Expression of p38 has also been shown to drive chemotherapy resistance in different cancers. 33,34 Similarly, the high ERK 1/2 and p38 activation level following chemotherapy treatment could indicate an enhanced pro-survival signaling response in the peripheral blood leukemic blasts.…”
Section: Healthy Donorsmentioning
confidence: 99%